Endophytic Cryphonectriaceae on native Myrtales: Possible origin of Chrysoporthe canker on plantation-grown Eucalyptus. Issue 6 (June 2016) - Mausse-Sitoe, Silvia N.D.; Rodas, Carlos A.; Wingfield, Michael J.; Chen, ShuaiFei; Roux, Jolanda
Abstract: Chrysoporthe austroafricana (Cryphonectriaceae) is a damaging canker pathogen on Eucalyptus species in Southern Africa. Recent studies have shown that the fungus occurs on native Syzygium species and that it has apparently undergone a host range expansion from these native trees to infect non-native Eucalyptus . The aim of this study was to consider whether Chr. austroafricana and other Cryphonectriaceae might exist as endophytes in native Myrtaceae, providing a source of inoculum to infect non-native Myrtales. Healthy branches were collected from Myrtaceae in Mozambique, incubated in florist foam, allowed to dry gradually and monitored for the appearance of fruiting bodies resembling species in the Cryphonectriaceae. Isolates were identified based on DNA sequence data. Two species in the Cryphonectriaceae were obtained, representing the first evidence that species in the Cryphonectriaceae occur as endophytes on native Myrtales, thus providing a source of inoculum to infect non-native and susceptible trees. This has important implications regarding the movement of planting stock used by ornamental tree and forestry enterprises.